If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 63 + -8x = 207 Solving 63 + -8x = 207 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-63' to each side of the equation. 63 + -63 + -8x = 207 + -63 Combine like terms: 63 + -63 = 0 0 + -8x = 207 + -63 -8x = 207 + -63 Combine like terms: 207 + -63 = 144 -8x = 144 Divide each side by '-8'. x = -18 Simplifying x = -18
| A-3b=70 | | 8n+4n^2-8n= | | 5(2a-3)=3(8+3a) | | -6y-8y-y= | | p+p-39=p+35 | | 7t+8=3t-12t | | ine^8/6 | | 23x-4-19x=2(2x-3)+2 | | w-25+w=w+34 | | 4(4a-3)=2(5+3a) | | 1/2=2Y | | x-11x+28=0 | | u+13+u+5=u+45 | | 12x+x^2=68 | | 110=3a+b | | s^2-2s=24+3s | | 3y=-9x+12 | | 15+5(z+3)=4z+3 | | 4s^2+14s-14s-49=0 | | A-3b+3a+b=180 | | 72-x^2=6x | | 45b^2+180b+100= | | 7(2a-3)=3(2+a) | | 4k^2-28k-49=0 | | 5r+8s-2(3r-6s)= | | 12s+4=45s | | 4+x+5x=8 | | x-42+x-33=x | | (2(cos^2)x)+7sinx+5=0 | | -2b-3b+7+9b=b+16 | | 6x-30=6x+20 | | -3(4y-9)+2(2y+5)= |